2016
DOI: 10.1159/000451062
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Recurrence of Macular Edema after Intravitreal Ranibizumab in Patients with Branch Retinal Vein Occlusion

Abstract: The aqueous humor levels of cytokines and growth/inflammatory factors were measured in 46 branch retinal vein occlusion (BRVO) patients with macular edema (ME) who were treated with intravitreal ranibizumab injection (IRI). Patients with recurrence of ME received further IRI as needed. The number of IRIs was significantly correlated with age, baseline best-corrected visual acuity, and baseline central macular thickness (CMT), as well as the baseline aqueous levels of 5 cytokines/factors (soluble vascular endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…That is, VEGF is inhibited by anti-VEGF agents, leading to decrease of leukocyte rolling and adhesion (leukostasis) that prevents the positive feedback loop from being established. We have previously reported that the number of doses of anti-VEGF therapy is significantly correlated with the baseline aqueous levels of inflammatory cytokines (sICAM-1, IL-6, and IL-8) [74]. Therefore, early initiation of anti-VEGF therapy should be considered to block positive feedback before macular edema becomes chronic.…”
Section: Possible Mechanism Of Macular Edema In Brvomentioning
confidence: 99%
“…That is, VEGF is inhibited by anti-VEGF agents, leading to decrease of leukocyte rolling and adhesion (leukostasis) that prevents the positive feedback loop from being established. We have previously reported that the number of doses of anti-VEGF therapy is significantly correlated with the baseline aqueous levels of inflammatory cytokines (sICAM-1, IL-6, and IL-8) [74]. Therefore, early initiation of anti-VEGF therapy should be considered to block positive feedback before macular edema becomes chronic.…”
Section: Possible Mechanism Of Macular Edema In Brvomentioning
confidence: 99%
“…However, recurrence of macular edema is frequent after one dose of IRI. We previously reported that the aqueous humor levels of several inflammatory factors are related to the severity of macular edema [11] and that the number of IRIs was significantly correlated with the baseline aqueous levels of several inflammatory factors [12], suggesting that inflammation may be involved in the recurrence of macular edema. However, it is unclear whether retinal blood flow is involved in the recurrence of macular edema and whether inflammation and inflammatory factors are involved in retinal blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…When Noma and others studied the correlation between aqueous factors and number of IVR injections needed to control ME recurrence during an observation period of 6 months, some pro-inflammatory cytokines (including IL-6, 8, etc.) but not VEGF were found to be correlated with the number of IVR injections ( Noma et al, 2016a ; Noma et al, 2021 ).…”
Section: Intraocular Biomarkersmentioning
confidence: 87%
“…Kotake et al noted that two monthly injections of intravitreal aflibercept (IVA) significantly downregulated aqueous IL-8 but IVR did not, suggesting a stronger inhibitory effect of IVA than IVR on aqueous IL-8 ( Kotake et al, 2019 ). Moreover, baseline IL-8 levels were found to be correlated with the number of IVR injections needed during a 6-month period with a “1 + PRN” regimen for BRVO ( Noma et al, 2016a ; Noma et al, 2021 ), which suggested the potential role of aqueous IL-8 as a predictor for ME recurrence.…”
Section: Intraocular Biomarkersmentioning
confidence: 92%
See 1 more Smart Citation